Health care services to diabetics in the territory of the Lha Napoli 2: quality perceived (Italian Journal of Public Health, 2007)
Background: Worldwide, diabetes mellitus is a chronic disease which now appears to be substantially increasing especially in industrialized countries. In recent years important improvements have been achieved in the treatment of the disease and the prevention of complications, but adherence of health care workers to these indicators varies considerably and often the results are inadequate. Our study relates to health care services supplied to diabetics within the territory of LHA (Local Health Agency) Napoli 2 in Italian region of Campania. The results obtained from 3 district areas were then compared.Methods: The prevalence study was carried out by interviewing diabetes-affected patients (aged 18-64) in the territory examined. For each area, a representative number of patients was selected through simple casual sampling.Results: A minimal knowledge of risk factors associated with diabetes in respect to those registered at a national level, an incomplete adherence to recommended actions, a good perception of the quality of healthcare services and a good level of information were recorded from all of the 462 subjects interviewed.Conclusions: This study draws attention to the critical aspects in healthcare services supplied to diabetics. The data collected could be useful to more effective and efficient strategies of “disease management” resulting in the better allocation of resources.